Parents’ Representations of Citizenship Formation: A Mixed Methods Analysis of Sociopolitical, Sociocultural, Socio-affective and Socioeconomic Dimensions in Primary Schools in the City of Trujillo - PAJUELO-ABANTO, MILUSKA JACKELINE MADELAINE; GASTAÑADUI-YBAÑEZ , LYLI ANA; COLINA-CUEVA, LUIS ALBERTO; ALANYA-PEREYRA, VÍCTOR EDUARDO; ALVAREZ-TRUJILLO, JOSÉ EMILIO; DIAZ-CASTILLO., VIOLETA ASUNCIÓN; GONZALES-PACHECO , ANTHONY JOEL; VÁSQUEZ-MONDRAGÓN, CECILIA DEL PILAR (Journal of Posthumanism, 2025)
This study examined citizenship representations among 52 elementary school parents in Trujillo, Peru, using convergent mixed-methods analysis across sociopolitical, sociocultural, socio-affective, and socioeconomic dimensions. Parents prioritized relational values (respect 87.2%, responsibility) over individual freedoms, employed family dialogue universally (100%) for decision-making, and demonstrated strong support for formal civic education (94.2%). Qualitative analysis revealed six emergent themes emphasizing emotional scaffolding and cultural transmission. Findings document a distinctive ’everyday citizenship’ paradigm grounded in familial dialogue and community values, contrasting with Western models emphasizing formal political participation. Results inform culturally appropriate civic education programs recognizing family strengths in democratic socialization.